2002
DOI: 10.1021/ja027411v
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Enantioselective Catalytic Intramolecular Stetter Reaction

Abstract: A family of chiral triazolium salts has been developed for inducing the asymmetric intramolecular Stetter reaction. The use of an aminoindanol-derived catalyst affords optimal results, with the product keto esters formed in 82-97% ee and very good chemical yield. Aromatic and aliphatic aldehydes are equally competent substrates for this reaction. The reaction conditions are reasonably mild and allow the isolation of the newly formed stereocenter without epimerization, although the presumed carbenic intermediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
154
0
8

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 498 publications
(163 citation statements)
references
References 21 publications
1
154
0
8
Order By: Relevance
“…In our initial communication, 5 we reported that the asymmetric intramolecular Stetter reaction may be catalyzed by 20 mol% of triazolium salts 4 and 6 utilizing 20 mol% KHMDS as base in xylenes. Catalysts 4, 5, 6 and 7 each provide the Stetter adducts with good selectivity.…”
Section: Resultsmentioning
confidence: 99%
“…In our initial communication, 5 we reported that the asymmetric intramolecular Stetter reaction may be catalyzed by 20 mol% of triazolium salts 4 and 6 utilizing 20 mol% KHMDS as base in xylenes. Catalysts 4, 5, 6 and 7 each provide the Stetter adducts with good selectivity.…”
Section: Resultsmentioning
confidence: 99%
“…The compatibility of other simple bases with the methodology was then evaluated: at 4 mol% catalyst loading (3.2 mol% base) Li 2 CO 3 , Na 2 CO 3 and NaHCO 3 proved completely ineffective (entries 10-12), while KHCO 3 and K 2 CO 3 furnished promising product yields of 32 and 42%, respectively, under identical conditions (entries 13 and 14). Optimisation of the loading of both catalyst and base using K 2 CO 3 led to conditions under which 6 could be obtained in up to 58% yield (entries [14][15][16][17][18][19][20]; however, this methodology was unsatisfactory due to a difficulty in arriving at a system of acceptable reproducibility (i.e. <5% discrepancy in yield between runs), despite considerable experimentation (>150 iterative runs) and the rigorous exclusion of air, moisture, etc.…”
Section: Catalyst Evaluation and Optimisation Of Conditionsmentioning
confidence: 99%
“…[2,5] Miller has devised several new functional peptides that catalyze the kinetic resolution of selected secondary alcohols [6] as well as a variety of other transformations. [7] Other noteworthy examples of organic catalysts include those of Fuji, [8] Spivey, [9] Oriyama, [10] Vedejs, [11] Breslow, [12] Enders, [13] and Rovis [14] as well as extensive studies of biocatalysts.[15]We were recently challenged to develop effective organic polymerization reactions in an effort to develop new materials for microelectronics, where residual metals must be avoided. During our initial survey of a variety of organic catalysts for the ring-opening polymerization (ROP) of cyclic esters we showed that nucleophilic catalysts such as tertiary amines, [16] phosphines [17] and stabilized singlet carbenes were effective polymerization catalysts for strained cyclic esters.…”
mentioning
confidence: 99%